2024
DOI: 10.3389/fnut.2023.1171775
|View full text |Cite
|
Sign up to set email alerts
|

Study from the United States: increased prevalence of kidney stones in patients with high weight-adjusted waist index

Zhaohua Gui,
Longshan Yu,
Yan Chen
et al.

Abstract: ObjectiveUsing data from NHANES 2007–2018, to examine the association between WWI (weight-adjusted waist index) index and prevalence of kidney stones.MethodsUsing multiple logistic regression analysis of the National Health and Nutrition Examination Survey (NHANES) 2007–2018, we evaluated the association between WWI index and the prevalence of kidney stones, followed by subgroup analysis of sensitive populations. Smooth curve fitting was used to determine whether there was a non-linear relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, the validity of these indicators needs to be confirmed by more extensive clinical studies. In recent years, it has been found that WWI is a superior predictor of non-alcoholic fatty liver disease [ 33 ], low cognitive performance [ 27 ], hyperuricemia [ 28 ], diabetic kidney disease [ 42 ], kidney stones [ 30 ], stress urinary incontinence [ 31 ], and depressive symptoms [ 43 ]. WWI has excellent potential as an anthropometric indicator because of its easy computation and strong ability to forecast disease onset [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the validity of these indicators needs to be confirmed by more extensive clinical studies. In recent years, it has been found that WWI is a superior predictor of non-alcoholic fatty liver disease [ 33 ], low cognitive performance [ 27 ], hyperuricemia [ 28 ], diabetic kidney disease [ 42 ], kidney stones [ 30 ], stress urinary incontinence [ 31 ], and depressive symptoms [ 43 ]. WWI has excellent potential as an anthropometric indicator because of its easy computation and strong ability to forecast disease onset [ 44 ].…”
Section: Discussionmentioning
confidence: 99%